Clinical and patient‐centered outcomes post non‐surgical periodontal therapy with the use of a non‐injectable anesthetic product: A randomized clinical study. Issue 4 (28th July 2019) - Marconcini, Simone; Goulding, Marilyn; Oldoini, Giacomo; Attanasio, Chiara; Giammarinaro, Enrica; Genovesi, Annamaria
Abstract: Aim: The aim of this study was to determine the impact of different full‐mouth decontamination (FMD) protocols on the effectiveness of an intrapocket anesthetic gel in periodontal maintenance patients. Methods: Patients undergoing the periodontal maintenance program and with the need for FMD participated in this study. Patients were randomly allocated to non‐surgical periodontal therapy (NSPT) with either a preparatory 15‐day decontamination phase, including chlorhexidine mouth rinse and domiciliary hygiene instructions (modified FMD: test group), or without it (FMD: control group). In both groups, NSPT was performed with the aid of a non‐injectable anesthetic gel. Clinical and patient‐related outcomes were recorded during a 6‐month follow‐up period. Results: Sixty patients completed the 6‐month study. Both groups experienced relevant clinical improvements after NSPT, but the test group showed a significant change in periodontal parameters already after the initial 15‐day preparatory period, and overall significantly better results in periodontal outcomes when compared with the control group at the last 6‐month follow up: the gingival index was 2.07 ± 1.25 in the control group and 1.13 ± 0.51 in the test group. Less pain and dental‐related anxiety were perceived by patients in the test group showing a 6‐month mean visual analog scale of 2.13 ± 1.25 in the control group and 1.13 ± 0.83 in the test group. Conclusion: The present study suggested that the modification of the standard FMD could improve the clinical efficacy of non‐injectable anesthetic, along with patients' short‐ and mid‐term appreciation and compliance.